((49 - 4)/90 - (16 - 1)/90 + 4/9)/((46 - 4)/90) - ((81 - 8)/90 - (53 - 5)/90)·24/100=
=(1/2 - 1/6 + 4/9)/(7/15) - (73/90 - 8/15)·24/100=
=7/9/(7/15) - 5/18·24/100=
=5/3 - 5/18·24/100=
=5/3 - 20/3/100=
=5/3 - 1/15=
=8/5
==========================================================
$\small \left(0,4\overline9-0,1\overline6+0,\overline4\right) : 0,4\overline6-\left(0,8\overline1-0,5\overline3\right)×0,24 =$
$\small =\left(\dfrac{49-4}{90}-\dfrac{16-1}{90}+\dfrac{4-0}{9}\right) : \dfrac{46-4}{90}-\left(\dfrac{81-8}{90}-\dfrac{53-5}{90}\right)×\dfrac{\cancel{24}^6}{\cancel{100}_{25}} =$
$\small =\left(\dfrac{\cancel{45}^1}{\cancel{90}_2}-\dfrac{\cancel{15}^1}{\cancel{90}_6}+\dfrac{4}{9}\right) : \dfrac{\cancel{42}^7}{\cancel{90}_{15}}-\left(\dfrac{73}{90}-\dfrac{\cancel{48}^8}{\cancel{90}_{15}}\right)×\dfrac{6}{25} =$
$\small =\left(\dfrac{1}{2}-\dfrac{1}{6}+\dfrac{4}{9}\right) : \dfrac{7}{15}-\left(\dfrac{73}{90}-\dfrac{8}{15}\right)×\dfrac{6}{25} =$
$\small =\left(\dfrac{9-3+8}{18}\right)·\dfrac{15}{7}-\left(\dfrac{73-48}{90}\right)×\dfrac{6}{25} =$
$\small =\dfrac{\cancel{14}^2}{\cancel{18}_6}·\dfrac{\cancel{15}^5}{\cancel7_1}-\dfrac{\cancel{25}^1}{\cancel{90}_{15}}×\dfrac{\cancel6^1}{\cancel{25}_1} =$
$\small =\dfrac{2}{6}·\dfrac{5}{1}-\dfrac{1}{15}×\dfrac{1}{1} =$
$\small =\dfrac{\cancel{10}^5}{\cancel6_3}-\dfrac{1}{15}=$
$\small =\dfrac{5}{3}-\dfrac{1}{15}=$
$\small =\dfrac{25-1}{15}=$
$\small =\dfrac{\cancel{24}^8}{\cancel{15}_5}= \dfrac{8}{5}$